Divergent roles for the IL-1 family in gastrointestinal homeostasis and inflammation - Lavelle, Edward; Finlay, Conor; Mc Entee, Craig (My University, 2019)
Inflammatory disorders of the gastro-intestinal tract are a major cause of morbidity and significant burden from a health and economic perspective in industrialized countries. While the incidence of such conditions has a strong environmental component, in particular dietary composition, epidemiological studies have identified specific hereditary mutations which result in disequilibrium between pro- and anti-inflammatory factors. The IL-1 super-family of cytokines and receptors is highly pleiotropic and plays a fundamental role in the pathogenesis of several auto-inflammatory conditions including rheumatoid arthritis, multiple sclerosis and psoriasis. However, the role of this super-family in the etiology of inflammatory bowel diseases remains incompletely resolved despite extensive research. Herein, we highlight the currently accepted paradigms as they pertain to specific IL-1 family members and focus on some recently described non-classical roles for these pathways in the gastrointestinal tract. Finally, we address some of the shortcomings and sources of variance in the field which to date have yielded several conflicting results from similar studies and discuss the potential effect of these factors on data interpretation.
PUBLISHED
cited By 0
Keywords: Cytokine; Inflammation immunomodulation; Gastrointestinal; Interleukin-1; Inflammatory bowel conditions